PENERAPAN MODEL PEMBELAJARAN DOUBLE LOOP PROBLEM SOLVING DALAM MENINGKATKAN MINAT BELAJAR FIQIH PADA SISWA KELAS VIII MTS MIFTAHUL ULA PEMATANG CENGAL - Suhaila Albi; Ahmad Zaki; Muhammad Saleh (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
This study aims to improve students' understanding in class VIII MTs Al-Jamiyatul Chalidiyah Stabat by using the Hypnotahfidz Academy Method to improve memorization of the Qur'an. This research uses a type of research, namely Classroom Action Research with two cycles and each cycle consists of four stages including planning, action, observation, and reflection. The subjects of this study were students of class VIII-A with a total of 26 students. Based on the results of the research, using the Hypnotahfidz Academy method can increase the memorization of the Qur'an in class VIII-A MTs Al-Jamiyatul Chalidiyah Stabat. In cycle I, it can be seen that the results of increasing student memorization were obtained from 26 students who had achieved learning mastery of 15 students and students who did not achieve learning mastery of 11 students with a percentage of 57.69% and could be included in the sufficient criteria. In cycle II, students have shown an increase in good results of memorizing the Koran, with 24 students achieving mastery learning and 2 students not achieving mastery learning with a learning mastery percentage of 92.30% and included in very good criteria. In cycle I and cycle II, students' memorization using the Hypnotahfidz Academy method has increased and the increase is 34.61%. Based on these results, it can be concluded that the application of the Hypnotahfidz Academy method can increase the memorization of the Koran for class VIII MTs Al-Jamiyatul Chalidiyah Stabat